PENGEMBANGAN MEDIA ELEKTRONIK LKPD BERBASIS SEARCH, SOLVE, CREATE, AND SHARE UNTUK MENDUKUNG PEMBELAJARAN KIMIA HIDROKARBON - Nurmala, Septa; Fatisa, Yuni (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
AbstractThis research was instigated by the teacher difficulty at school in implementing the appropriate learning method in online learning process. This research aimed at designing SSCS (Search, Solve, Create, and Share) based student electronic worksheet on Hydrocarbon lesson, and finding out validity and practicality SSCS based student electronic worksheet as a teaching material on Hydrocarbon lesson. This study uses the Borg and Gall development model, which only takes 5 out of 10 stages, namely data collection, planning, product development, initial trials and initial product revisions. Preliminary testing was conducted at State Senior High School 5 Tapung by a Chemistry subject teacher and 10 of the eleventh-grade students of MIA. The data obtained were analyzed by using quantitative descriptive analysis technique. The data analysis result of validity test showed that the percentages were 97.14% by media experts with very valid category and 92.5% by material experts with very valid category. In practicality test by teachers, the percentage was 95.71% with very practical category, and the percentage of student response test was 54% with practical enough category. However, this research still has some shortcomings so it is expected that in the future an effectiveness test will be carried out to determine the effectiveness of the media. This research is expected to help the learning process.Keywords : Student Electronic Worksheet, SSCS, Hydrocarbon